Endovascular thrombectomy first-pass reperfusion and ancillary device placement - Navia, Pedro; Espinosa de Rueda, Mariano; Rodriguez-Benitez, Amado; Ballenilla Marco, Federico; Pumar, José Manuel; Gallego-Leon, Jose Ignacio; Diaz-Valiño, Jose Luis; Mendez, Jose Carlos; Hernández Fernández, Francisco; Rodriguez-Paz, Carlos Manuel; Hernandez, David; Maynar, Franscisco Javier; et al. (Journal of neurointerventional surgery, 2024)
BackgroundRecent randomized trials have demonstrated the efficacy of mechanical thrombectomy in treating acute ischemic stroke, however, further research is required to optimize this technique. We aimed to evaluate the impact of guide catheter position and clot crossing on revascularization rates using A Direct Aspiration First Pass Technique (ADAPT).MethodsData were collected between January 2018 and August 2019 as part of the Spanish ADAPT Registry on ACE catheters (SARA), a multicenter observational study assessing real-world thrombectomy outcomes. Demographic, clinical, and angiographic data were collected. Subgroup analyses assessed the relationship between guide catheter/microguidewire position and modified Trombolysis in Cerebral Infarction (mTICI) scores. First pass effect (FPE) was defined as mTICI 3 after single pass of the device.ResultsFrom a total of 589 patients, 80.8% underwent frontline aspiration thrombectomy. The median score on the National Institutes of Health Stroke Scale (NIHSS) was 16.0. After adjusting for confounders, the likelihood of achieving FPE (adjusted Odds Ratio (aOR), 0.587; 95% confidence interval (CI), 0.38 to 0.92; p=0.0194) were higher among patients with more distal petrocavernous placement of guide catheter. The likelihood of achieving FPE (aOR, 0.592; 95% CI, 0.39 to 0.90; p=0.0138) and final angiogram complete reperfusion (aOR, 0.465; 95% CI, 0.30 to 0.73; p=0.0008) were higher among patients without microguidewire crossing the clot. No difference was noted for time from arterial puncture to reperfusion in any study group. At the 90-day follow-up, the mortality rate was 9.2% and 65.8% of patients across the entire study cohort were functionally independent (modified Rankin Scale (mRS) 0–2).ConclusionsPetrocavernous guide catheter placement improved first-pass revascularization. Crossing the occlusion with a microguidewire lowered the likelihood of achieving FPE and complete reperfusion after final angiogram.